Ecology and Genetic Identification of Freshwater Turtles in Pakistan - Qayash Khan, Muhammad; Hafsa Zahid, Yaseen; Numan, Muhammad; da Silva Vaz Jr., Itabajara; Ali, Abid (Acta Scientiae Veterinariae, 2021)
Background: The turtle population plays an important role in sustaining the water ecosystem by minimizing pollution from water. The identification and molecular investigation of freshwater fauna is essential for conservation of the species that are near to extinction. The quality of water, type of flora, fauna, and environmental condition are the major factors that directly affect the distribution of freshwater turtles. Studies on the species diversity and habitat of freshwater turtle have not been focused previously in the region. The present study was the first conducted to estimate the habitat and genetic diversity of freshwater turtles using 12S rRNA (ribosomal RNA) gene in Pakistan. Materials, Methods & Results: A total of 26 samples were collected from various localities using hand net, cast net, gills net, steel hooks, thick chemical wire, using chicken intestine and small fishes. The collected turtle specimens were morpho-taxonomically categorized into two genera, Lissemys punctata andersoni (n=13, 50%) and Nilssonia gangetica (n=13, 50%). The collected species showed an aggressive and active behavior in captivity during summer. Genomic DNA was extracted from collected specimens and used in PCR reaction by using specific primers for the amplification of short fragments of 12S rRNA gene. Analysis of generated sequences confirmed the existence of L. p. andersoni in the region. The generated sequences of L. p. andersoni correspond to Clad A and showed a close resemblance among different species of the genus Lissemys. Discussion: This study is the first investigation about the habitat and of the endemic turtle species L. p. andersoni and N. gangetica in Pakistan. The genetic identification followed by phylogenetic analysis based on 12S rRNA partial genes revealed a closest similarity with the sequences generated for the same species from the neighboring countries. This study provided information to conduct further molecular studies that are essential to provide significant genetic data about turtle species. Keywords: turtle, ecology, diversity, phylogeny, Pakistan.